Association of geographical disparities and segregation in regional treatment facilities for Black patients with aneurysmal subarachnoid hemorrhage in the United States - Kabangu, Jean-Luc K.; Fry, Lane; Bhargav, Adip G.; De Stefano, Frank A.; Bah, Momodou G.; Hernandez, Amanda; Rouse, Adam G.; Peterson, Jeremy; Ebersole, Koji; Camarata, Paul J.; Eden, Sonia V. (Frontiers in Public Health, 2024)
Background and objectives This study investigates geographic disparities in aneurysmal subarachnoid hemorrhage (aSAH) care for Black patients and aims to explore the association with segregation in treatment facilities. Understanding these dynamics can guide efforts to improve healthcare outcomes for marginalized populations. Methods This cohort study evaluated regional differences in segregation for Black patients with aSAH and the association with geographic variations in disparities from 2016 to 2020. The National Inpatient Sample (NIS) database was queried for admission data on aSAH. Black patients were compared to White patients. Segregation in treatment facilities was calculated using the dissimilarity (D) index. Using multivariable logistic regression models, the regional disparities in aSAH treatment, functional outcomes, mortality, and end-of-life care between Black and White patients and the association of geographical segregation in treatment facilities was assessed. Results 142,285 Black and White patients were diagnosed with aSAH from 2016 to 2020. The Pacific division (D index = 0.55) had the greatest degree of segregation in treatment facilities, while the South Atlantic (D index = 0.39) had the lowest. Compared to lower segregation, regions with higher levels of segregation (global F test p < 0.001) were associated a lower likelihood of mortality (OR 0.91, 95% CI 0.82–1.00, p = 0.044 vs. OR 0.75, 95% CI 0.68–0.83, p < 0. 001) (p = 0.049), greater likelihood of tracheostomy tube placement (OR 1.45, 95% CI 1.22–1.73, p < 0.001 vs. OR 1.87, 95% CI 1.59–2.21, p < 0.001) (p < 0. 001), and lower likelihood of receiving palliative care (OR 0.88, 95% CI 0.76–0.93, p < 0.001 vs. OR 0.67, 95% CI 0.59–0.77, p < 0.001) (p = 0.029). Conclusion This study demonstrates regional differences in disparities for Black patients with aSAH, particularly in end-of-life care, with varying levels of segregation in regional treatment facilities playing an associated role. The findings underscore the need for targeted interventions and policy changes to address systemic healthcare inequities, reduce segregation, and ensure equitable access to high-quality care for all patients.